La importancia de la creatividad a través del uso del juego didáctico en los niños de 5 años de la Unidad Educativa Elia Liut de la parroquia de Aloasi - Izurieta Guzmán, Fátima Mireya (2023)
This thesis determines the importance of creativity through the use of didactic games in 5-year-old boys and girls, it is intended to develop a didactic guide to stimulate creativity through the use of didactic games in 5-year-old boys and girls. of initial education of the Elia Liut Educational Unit in the parish of Aloasi. 7 playful activities are proposed: group work of art, puppets with recyclable material, the musical band, the story that you like the most, drops of color, circles and corridors, imitate the drawing. These will allow to be a playful methodological tool of great importance in the teaching process in children of initial education, it will allow to strengthen creativity and meaningful learning. The Mixed approach is used as a methodology, with its exploratory and inductive research methods.